Maximizing maize grain yield stability through integrated management of plant density and hybrid reproductive plasticity - Martinez, Dionisio Roberto (2026)
Context: The plant density that maximizes grain yield is influenced by environmental conditions and the hybrid’s sensitivity to low resource availability and reproductive plasticity. Rainfall variability across seasons introduces uncertainties in determining optimal plant density, even in humid regions with typically high-yielding environments. Objective: This study aimed to identify management strategies that integrate plant density and genotypes with varying reproductive plasticity levels to maximize grain yield and stability across environments with differing rainfall in a humid temperate area where maize is commonly grown. Methods: This study involved experiments conducted across multiple locations and seasons, testing combinations of three plant densities (8, 6, and 4 plants m⁻²) with three hybrids exhibiting contrasting reproductive plasticity (high prolificacy, high ear flex, and moderate prolificacy with ear flex). Stability analyses were performed using Eberhart and Russell, Shukla, and Genotype by Environment (GGE) biplot methods. Results: The environments in this study ranged from 9500 to 14000 kg ha⁻¹ , with 61 % of variability attributed to rainfall differences. In moderately yielding environments, reducing plant density (from 8 to 6 or 8–4 plants m−2) had no effect on grain yield. However, significant declines were observed in high and low-yielding environments with large reductions in plant density (up to ≈20 % and 40 % declines, respectively). The highest yield stability across environments was achieved with high or medium plant density management and hybrids exhibiting high reproductive plasticity, while low-density management resulted in the lowest stability. Conclusion: The grain yield response to reduced plant density varies with the degree of reduction and the environment, irrespective of hybrid reproductive plasticity. In this humid region without severe water limitations and for the genotypes used in this study, combining high or medium plant density with hybrids exhibiting high reproductive plasticity maximizes and stabilizes grain yields across environments with varying rainfall.